Ergonomics and Library Professionals: a Study - Ally Sornam, S.; Issac Arputharaj, J.; Mahalakshmi, K. (Journal of Information and Knowledge, 2011)
Workplace stress has always been a source of consideration for organization that seeks to foster satisfied and motivated environment. Ergonomics, the science related to man and his work helps to design workstations and tools. The present study has made an attempt to identify the impact of ergonomics on academic library professionals. It has revealed that academic library professionals‟ perception on ergonomics is low. But they have shown problems associated with ergonomics with regard to IT tools, working posture, etc.